(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Contemporary Indian philosopher Swami Vivekananda has articulated a distinctive interpretation on the concept of religion. He advocated for the imperative of a global religion or the embrace of religious diversity. He asserts that religion transcends mere discourse on concepts or theories, and is not synonymous with sectarianism. It is a connection between the soul and the divine. He elucidated that religion is not comprised of constructing temples, creating churches, or participating in communal worship. Religion is not defined by adherence to a specific doctrine or belief but by spiritual enlightenment. Swami Vivekananda was inspired by and affected by India’s ancient culture and philosophy, which is evident in all his messages and teachings, as they are fundamentally based in the philosophy of the Upanishads. He extracted numerous concepts from Vedanta philosophy, which encompasses not only metaphysics but also possesses social and practical ramifications in human existence. Universal religion can be described as the most comprehensive idea that elucidates the inherent oneness and distinctive essence of all global faiths. The fundamental essence of all world faiths is identical. Universal religion articulates the uniformity of the foundational ideas and doctrines inherent in all global religions. Swami Vivekananda posits the existence of a global religion. Just as the worldwide brotherhood of humanity exists, so too does a universal religion. It should be noted that Universal religion is neither the result of divergent comprehension nor a synthesis of the essential components of other religions. It is the recognition that various religions are manifestations of a singular fundamental truth. In this article, views, role and perspectives of Swami Vivekananda’s philosophy towards universal religion has been discussed.